Trójjęzyczność ukraińsko-rosyjsko-polska Ukraińców niepolskiego pochodzenia - Levchuk, Pavlo (2020)
UKRAINIAN-RUSSIAN-POLISH TRILINGUALISM OF UKRAINIAN PEOPLE OF NON-POLISH DESCENT The dissertation concerns the phenomenon so far not subjected to studies of trilingualism of Ukrainians living both in Poland and in Ukraine. The study was attended by non-Polish descent persons, for whom Polish is a foreign language. The research was carried out in the years 2015-2017 in Ukraine and Poland and 1,160 people took part in it.The last chapter consists of the summary of the presented research, that apart from the analysis of the functioning of trilingualism concerning the use of the Polish language, points, for the first time, at the value of the Polish language for people of non-Polish descent. For those people Polish language slowly becomes a tool for self-fulfilment of an increasing number of people.